2019
DOI: 10.1038/s41598-018-36485-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for lyssavirus persistence in non-synanthropic bats in Europe: insights from a modeling study

Abstract: Bats are natural reservoirs of the largest proportion of viral zoonoses among mammals, thus understanding the conditions for pathogen persistence in bats is essential to reduce human risk. Focusing on the European Bat Lyssavirus subtype 1 (EBLV-1), causing rabies disease, we develop a data-driven spatially explicit metapopulation model to investigate EBLV-1 persistence in Myotis myotis and Miniopterus schreibersii bat species in Catalonia. We find that persistence relies on host spatial structure through the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…As with [32], the lack of validation of the [33] model against field-derived data made it impossible to assess its validity. [43] compared simulations of spatially explicit, multi-species metapopulation models of EBLV-1 transmission in Miniopterus schreibersii and Myotis myotis with and without virus-induced mortality. The authors found support for an SEIRS model structure which assumed -as previously modeled by [32,33] no virus-induced mortality in bats infected with EBLV-1 (Figure 3).…”
Section: Lyssavirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…As with [32], the lack of validation of the [33] model against field-derived data made it impossible to assess its validity. [43] compared simulations of spatially explicit, multi-species metapopulation models of EBLV-1 transmission in Miniopterus schreibersii and Myotis myotis with and without virus-induced mortality. The authors found support for an SEIRS model structure which assumed -as previously modeled by [32,33] no virus-induced mortality in bats infected with EBLV-1 (Figure 3).…”
Section: Lyssavirusesmentioning
confidence: 99%
“…The authors found support for an SEIRS model structure which assumed -as previously modeled by [32,33] no virus-induced mortality in bats infected with EBLV-1 (Figure 3). However, in contrast to the purely simulation-focused studies discussed above, [43] then fit this SEIRS framework to data from a four-year field survey tracking EBLV-1 seroprevalence in Miniopterus schreibersii and Myotis myotis across two sites in Catalonia. They reported a range of R 0 estimates across their field system (from 0.53 to 1.6) and emphasized the need for cross-species mixing and spatial metapopulation structure in maintaining the virus in their system -with a pronounced role for M. schreibersii in sourcing infections across the metapopulation due to its migratory behavior and high population density in the system.…”
Section: Lyssavirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-population structure for Myotis myotis is described here for the first time, providing critical information to unravel dynamics of LYSVs in this bat species. Indeed, previous mathematical models suggested this bat was unable to sustain the circulation of EBLV-1 alone, supporting that sero-positivity in the Balearic Islands was likely associated with inter-species transmission from the highly vagile species Miniopterus scheibersii (Colombi et al, 2019;Pons-Salort et al, 2014). In South Tyrol, the greater mouse-eared bats form very large maternity colonies within churches, where the interaction with other species is strongly limited compared to the cave dwelling populations typical of the Mediterranean area.…”
Section: Discussionmentioning
confidence: 75%
“…In this context, the meta-population structure seen in our sampling area as opposed to the close population model in the Balearic Islands could explain virus maintenance in M. myotis even in the absence of M. schreibersii . Indeed, several studies suggest that the exchange of individuals between roosts may be one of the main factors favoring the persistence of viruses across the whole population, sometimes allowing for local fade out of infection with subsequent reintroduction (Blackwood, Streicker, Altizer, & Rohani, 2013;Colombi et al, 2019;Horton et al, 2020;Pons-Salort et al, 2014).…”
Section: Discussionmentioning
confidence: 99%